Possibilities of instrumental methods of diagnosis in choice of the treatment tactics in women–patients, suffering varicose dilation of the lower extremities and pelvic veins - О. E. Shved; О. І. Nabolotnyi; Yu. М. Hupalo; V. G. Gurianov (Клінічна хірургія)
Objective. To elaborate the algorithm for preoperative diagnosis of combined varicose dilation in the lower extremities (LE) and pelvis with the aim to select and use the elective planning of surgical treatment.